PENGARUH DIVIDEND PAYOUT RATIO, EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON ASSETS, TINGKAT INFLASI, DAN VOLUME PERDAGANGAN TERHADAP HARGA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Ulfah Maria; Yusralaini Yusralaini; Wiguna Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the influence of Dividend Payout Ratio,Earning per Share, Debt to Equity Ratio, Return on Assets, Inflation Rate andTrading Volume on stock prices of listed company in Indonesia Stock Excange(empirical studies on food and beverage companies in 2013-2017). The sample inthis study amounted to 10 companies manufacturing food and beverage sector.The method of determining the sample uses a purposive sampling method withcertain criteria. Data analysis techniques in this study used multiple linierregression and classic assumption tests which inculed normality test,multicolonearity, heteroscedasticity, and autocorrelation. The hypothesis wastested using t – statistics and use SPSS version 25.0 as the software for processingthe data. From the test results, there are four variables that have an influence onstock prices are : Dividend Payout Ratio, Earning per Share, Debt to EquityRatio, and Return on Assets. While the others two variabels, namely the inflationrate and trading volume do not have a significant effect on stock prices of listedcompany in Indonesia Stock Exchange.Keywords : Dividend Payout Ratio, Earning per Share, Debt to Equity Ration,Return on Assets, Inflation Rate, Trading volume, Stock Prices